Impact of Thyroid Cancers on Thyroid Hormones among Patients Attended Tripoli University Hospital - Salah Elbaruni; Magdoline Almehdawi; Lubna Badi; Najua Ferrara; Nidal Bilkhier (AlQalam Journal of Medical and Applied Sciences, 2024)
Thyroid cancer is one of the most common endocrine system malignancy, accounting for 3.8% of new cancer cases in the US and ranking ninth overall. The number of people diagnosed with thyroid cancer has increased dramatically over the last three decades, indicating the disease’s global severity. The purpose of this study was to determine the effect different types of thyroid cancers on thyroid hormones (TSH, T4 and T3). This study was conducted in the Oncology and Endocrinology departments of Tripoli University Hospital (TUH). A total of 70 thyroid cancer patients were targeted, and data was collected using patient record file. TSH, T4 and T3 levels monitored and analyzed in biochemistry laboratory using Cobas e411 Fully Automated Machin. Thyroid cancer struck most females than males. Thyroid cancer incidence has increased among people aged 20 to 40. Most thyroid cancer cases are papillary thyroid carcinoma. Thyroidectomy was done with an 87.14% success rate. The level of TSH hormones increased in thyroid cancer patients. Also, the percentage of T4 hormone levels was mostly increased, whereas thyroid cancer had no proven effect on T3. Papillary thyroid carcinoma was the most common thyroid cancer. There was pronounced effect of thyroid cancer on the TSH and T4 hormone, however T3 hormone remained unchanged. سرطان الغدة الدرقية هو أحد أكثر أمراض الغدد الصماء شيوعًا، حيث يمثل 3.8% من حالات السرطانات الجديدة في الولايات المتحدة ويحتل المرتبة التاسعة على إجمال السرطانات. خلال العقود الثلاثة الأخيرة لقد ارتفع أعداد حالات تشخيص سرطان الغدة الدرقية بشكل كبير، مما يشير إلى خطورة المرض على مستوى عالمي. هدفت هذه الدراسة إلى تحديد تأثير سرطانات الغدة الدرقية على مستوى هرمونات الغدة الدرقية ) TSH، T4، .(T3 تمت هذه الدراسة في قسمي الأورام والغدد الصماء في المستشفى الجامعة طرابلس، طرابلس، ليبيا. استهداف الدراسة 70 مريضًا بسرطان الغدة الدرقية، ولقد تم جمع البيانات باستخدام ملفات وسجلات المرضى. ولقد تم مراقبة وتحليل مستويات TSH، T4، وT3 في مختبر الكيمياء الحيوية باستخدام جهازCobas e411 Fully Automated. أثبتت الدراسة أن معظم مرضى سرطان الغدة الدرقية من الإناث مقارنة بالذكور، وأن اغلب المصابين بسرطان الغدة الدرقية تتراوح أعمارهم بين 20 و40 عامًا. أغلب حالات سرطان الغدة الدرقية من النوع سرطان الغدة الدرقية الحليمي. وصل عدد حالات استئصال كامل للغدة الدرقية بنسبة 87.14%. إرتفاع مستوى هرمون TSH عند مرضى سرطان الغدة الدرقية وكذلك إرتفاع نسبة مستوى هرمون T4، في حين أنه لم يُثبت تغير أو إرتفاع مستوى T3 لدى مرضى سرطان الغدة الدرقية. أظهرت هذه الدراسة أن نسبة الإصابة بسرطان الغدة الدرقية كان أعلى في الإناث من الذكور، وأكثر شيوعًا في الفئة العمرية من 20 إلى 40 عامًا. كما أن سرطان الغدة الدرقية الحليمي هو الأكثر شيوعًا. علاوة على ذلك، أظهرت نتائج هذه الدراسة أن تأثير سرطان الغدة الدرقية على مستوى هرمون TSH وهرمون T4 وكان مرتفع بشكل ملحوظ، مع عدم التأثير على هرمون T3